Naloxone injections into CA3 disrupt pattern completion associated with relapse from cocaine seeking. Issue 7 (22nd February 2016) - Kesner, Raymond P.; Kirk, Ryan A.; Clark, Jascha K.; Moore, Angela; Keefe, Kristen
ABSTRACT: The goal of the present research was to assess the degree to which a pattern completion process operates in cue‐induced relapse to cocaine‐seeking behavior. Using a novel cue‐preference version of the place preference task, rats were administered cocaine or saline, which resulted in a preference for the cocaine‐paired cues. After 21 days of abstinence and prior to the preference test, for one group, PBS or naloxone was injected into the CA3 subregion of the hippocampus and for a second group, saline or naloxone was injected systemically. The results indicated that infusions of naloxone into CA3 or systemic injections produced a marked disruption for one and two cues, but had minimal disruptive effect for three or four cues, suggesting that naloxone injections disrupt CA3 function and trigger a deficit in a pattern completion process. Thus, it appears that cue‐based activation of the dorsal CA3 might be a critical trigger via a pattern completion process. Based on additional analyses it appears that there is a disruption primarily for object touches for one cue naloxone injections into the CA3 or systemic injections, but no effect on time (spatial context). © 2016 Wiley Periodicals, Inc.